Morphology of Proximal Cortical Epiphysis Bone of Ovariectomized Rattus Norvegicus - Neng Nenden Mulyaningsih; Ariadne Lakshmidevi Juwono; Djarwani Soeharso Soejoko; Dewi Apri Astuti (Galenos Yayinevi, 2020)
Objective:Osteoporosis could affect anyone, both men and women and young and old. This study aimed to analyse the morphology of ovariectomy (OVX) to the proximal cortical epiphysis bone using scanning electron microscope (SEM) and transmission electron microscope (TEM) on ovariectomised rat models.Materials and Methods:The analysed bones were the cortical femur bones taken from ovariectomised female Rattus norvegicus. Characterisation was performed from the third week of OVX and continued at the fifth, seventh and ninth weeks. The analysis was focused on two levels of structure, including the microstructure level with a magnification of 100 μm, which was obtained from SEM images to analyse the shape and intensity of the bone cavity, and the nanostructure level with a magnification of 50 nm, which was obtained from TEM images to analyse the bone apatite crystals.Results:At the microstructure level, the cavity that appeared in 9-week-old ovariectomised rats was found to increase by 68.9% compared to that of the control group (non-OVX). In addition, at the nanostructure level, the plate, tablet and overlapping apatite crystals were present in both the non-OVX and OVX rats. However, a tendency of the tablet size of apatite crystals to decline was observed in the ovariectomised rats group.Conclusion:White female Rattus norvegicus showed osteoporosis conditions based on the morphology and percentage of cavities at 9 weeks of OVX. In addition, OVX lowered the size of apatite crystals.